Variation in sex determination and the application of the YY male technology for the production of all-male populations of the tilapia Oreochromis mossambicus - Jordaan, M. S. (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--University of Stellenbosch, 2004.